Faktor-faktor yang Memengaruhi Pendapatan Usahatani Jeruk di Desa Punten Kecamatan Bumiaji Kota Batu - Aprilia, Rosi Laili; Bakhtiar, Ary (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2026)
Apples are a well known and growing horticultural commodity in Batu City, but in recent years many apple farmers have converted their agricultural land into orange plantations. This change occurred due to several factors such as unstable apple price fluctuations, high production costs, and increasing outbreaks of apple pests and diseases which are challenges for farmers to overcome due to climate change. But on the contrary, orange plants are considered more adaptive to environmental conditions and have promosing market opportunities, making them a more rational choice for farmers. Most people in Punten Village use their agricultural land to farm oranges with various varieties. However, even though the production is quite high, optimizing farmers income still faces challenges. Therefore, farmers must study in depth the aspects that affect income in order to maximize their income. The purpose of this study was to identify factors that affect the income of citrus farming in Punten Village, Bumiaji District, Batu City. The population selection was taken by purposive sampling, namely apple farmers who switched to citrus farmers.The population obtained was 240 farmers and 36 farmers were selected randomly (random sampling). Multiple linear regression analysis was used in this study. Land area (X1), labor costs (X2), seed costs (X3), fertilizer costs (X4), pesticide cost (X5) became independent variables, and income (Y) as the dependent variable. The results showed that the variables of land area and seed costs had a significant and unidirectional influence on income.The variable of fertilizer costs had a significant but not unidirectional influence. Meanwhile, farmer income was not affected by the variables of labor costs and pesticide costs.